Imported endemic mycoses in Spain: Evolution of hospitalized cases, clinical characteristics and correlation with migratory movements, 1997-2014. - Daniel Molina-Morant; Adrián Sánchez-Montalvá; Fernando Salvador; Augusto Sao-Avilés; Israel Molina (Public Library of Science (PLoS), 2018)
Endemic mycoses are systemic fungal infections. Histoplasmosis is endemic in all temperate areas of the world; coccidioidomycosis and paracoccidioidomycosis are only present in the American continent. These pathogens are not present in Spain, but in the last years there has been an increase of reported cases due to migration and temporary movements. We obtained from the Spanish hospitals records clinical and demographic data of all hospitalized cases between 1997 and 2014. There were 286 cases of histoplasmosis, 94 of Coccidioidomycosis and 25 of paracoccidioidomycosis. Overall, histoplasmosis was strongly related to HIV infection, as well as with greater morbidity and mortality. For the other mycoses, we did not find any immunosuppressive condition in most of the cases. Although we were not able to obtain data about clinical presentation of all the cases, the most frequently found was pulmonary involvement. We also found a temporal correlation between the Spanish population born in endemic countries and the number of hospitalized cases along this period. This study reflects the importance of imported diseases in non-endemic countries due to migratory movements.